2021
DOI: 10.1186/s13102-021-00280-6
|View full text |Cite
|
Sign up to set email alerts
|

Sports nutrition knowledge and perceptions among professional basketball athletes and coaches in Lebanon-a cross-sectional study

Abstract: Background Basketball is the most popular sport in Lebanon. Adequate nutrition has been established to be a key component of optimal athletic performance, recovery from exercise and exercise-induced injury and documented to be associated with adequate nutrition knowledge (NK). In Lebanon, nutrition education is not incorporated into the basketball player training program and there is no established position for sports nutritionists in basketball clubs. To our knowledge, the present study is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 55 publications
(76 reference statements)
1
24
2
Order By: Relevance
“…Future research should collate detailed information on this, including the course level. Surprisingly, our data showed that university athletes who had never seen a dietitian/nutritionist had a higher knowledge score (61.5%) than their counterparts (55.6%), contradicting previous findings [ 8 ]. Yet, we did not collect information on the consultation sessions’ frequency, duration, and purpose, which could explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Future research should collate detailed information on this, including the course level. Surprisingly, our data showed that university athletes who had never seen a dietitian/nutritionist had a higher knowledge score (61.5%) than their counterparts (55.6%), contradicting previous findings [ 8 ]. Yet, we did not collect information on the consultation sessions’ frequency, duration, and purpose, which could explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies found significant differences in knowledge scores based on sex [ 5 , 8 , 26 ], BMI classification [ 26 ], and sports category [ 26 ], which we did not observe in this study. While the general principle of sports nutrition is universal for all athletes worldwide, different studies used different sets of questions and assessed different knowledge domains.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations